The cation and anion bonding modes make a difference: an unprecedented layered structure and a tri(hetero)nuclear moiety in thioantimonates(v). Issue 48 (1st December 2021) - Danker, Felix; Engesser, Tobias A.; Broich, Dario; Näther, Christian; Bensch, Wolfgang
Abstract : Mixing solutions of M 2+ (M = Cu 2+ or Zn 2+ ) salts containing cyclam as ligand and an aqueous solution of Na3 SbS4 ·9H2 O led to crystallization of two new compounds within minutes: [Cu(cyclam)]3 [SbS4 ]2 n ·20 n H2 O and [Zn(cyclam)]3 [SbS4 ]2 ·8H2 O. Abstract : Mixing solutions of M 2+ (M = Cu 2+ or Zn 2+ ) salts containing cyclam (cyclam = 1, 4, 8, 11-tetraazacyclotetradecane) as the ligand and an aqueous solution of Na3 SbS4 ·9H2 O at room temperature led to the crystallization of two new compounds within minutes: [Cu(cyclam)]3 [SbS4 ]2 n ·20 n H2 O (I ) and [Zn(cyclam)]3 [SbS4 ]2 ·8H2 O (II ). In the structure of I [SbS4 ] 3− anions acting as a tridentate ligand join CuN4 S2 octahedra generating twelve-membered rings by corner-sharing of SbS4 and CuN4 S2 units. The rings are condensed into layers, which are stacked onto each other in a 6R polytype manner. The layers contain large pores with the water molecules located between the layers above and below the pores. In contrast, the structure of II comprises a discrete molecular tri(hetero)nuclear moiety with a bidentate [SbS4 ] 3− anion connecting two rectangular pyramidal ZnN4 S polyhedra. The crystal water molecules of I and II can be thermally removed, and I and II are recovered by treatment under a humid atmosphere. The EPR spectrum of I indicates the presence of Cu 2+ cations, which is unusual in the environment of S 2− anions. The different bonding situations and the preferences for the coordination geometries of Cu 2+ and Zn 2+ cations are rationalized by DFT based calculations, demonstrating that Cu 2+ prefers an octahedral environment while Zn 2+ adopts the square-pyramidal coordination. The pronounced differences in the vibrational spectra are also analyzed with DFT, showing how the different modes are influenced by the differing bond strengths.